2019
DOI: 10.1530/eje-18-0782
|View full text |Cite
|
Sign up to set email alerts
|

Plasma steroid metabolome profiling for the diagnosis of adrenocortical carcinoma

Abstract: Objective: Current workup for the pre-operative distinction between frequent adrenocortical adenomas (ACAs) and rare but aggressive adrenocortical carcinomas (ACCs) combines imaging and biochemical testing. We here investigated the potential of plasma steroid hormone profiling by liquid chromatography tandem mass spectrometry (LC-MS/MS) for the diagnosis of malignancy in adrenocortical tumors. Design: Retrospective cohort study of prospectively collected EDTA-plasma samples in a single tertiary reference cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 28 publications
1
63
0
7
Order By: Relevance
“…Steroid hormones in cell culture supernatants of NCI-H295R and CU-ACC1 cells were quantified with the MassChrom steroids kit (Chromsystems) on a Qtrap 6500 + (Sciex) mass spectrometer coupled to a 1290 Infinity HPLC System (Agilent). Signal analysis was performed with Analyst Software (1.6.3, Sciex) as described elsewhere 61 .…”
Section: Lc-ms/ms Of Steroid Hormonesmentioning
confidence: 99%
“…Steroid hormones in cell culture supernatants of NCI-H295R and CU-ACC1 cells were quantified with the MassChrom steroids kit (Chromsystems) on a Qtrap 6500 + (Sciex) mass spectrometer coupled to a 1290 Infinity HPLC System (Agilent). Signal analysis was performed with Analyst Software (1.6.3, Sciex) as described elsewhere 61 .…”
Section: Lc-ms/ms Of Steroid Hormonesmentioning
confidence: 99%
“…Another useful tool would be using steroid profiling as an early diagnostic as well as prognostic marker. Initial data have been in favor of its use [71][72][73]; however, this tool is not prospectively validated, which limits its use in clinical practice. Based on the data we have regarding genetic markers in patients with ACC [41][42][43]74], using genetic profiling to predict recurrence risk is another important tool.…”
Section: Future Directionsmentioning
confidence: 99%
“…This so-called heterogeneity of steroidogenesis observed is a reflection of immature and dedifferentiated cell features, which are the hallmark of ACC [11,13,[15][16][17]. To our knowledge, no serum or urinary steroid metabolites associated with prognostic factors in ACC have been demonstrated to date, but several papers have reported these were useful for the diagnosis of ACC [11][12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, steroid profiling has emerged as a powerful novel diagnostic tool for ACC [11][12][13][14]. Previous reports demonstrated that examination of serum steroid metabolites using liquid chromatography tandem mass spectrometry (LC-MS/MS) [12,13] or urine steroid metabolites using gas chromatography mass spectrometry (GC-MS) [15][16][17][18][19] are useful for distinguishing ACC from adrenocortical adenoma. Furthermore, the ENSAT recommends a biochemical workup for suspected ACC that includes serum cortisol, aldosterone, 17-hydroxyprogesterone, dehydroepiandrosterone sulfate (DHEAS), androstenedione, testosterone, and 17-beta-estradiol (http://www.ensat.org/page-1317312).…”
Section: Introductionmentioning
confidence: 99%